Perancangan Sistem Informasi Pembelian dan Metode Berbasis Web Studi Kasus Toko Jam Tangan Menggunakan Metode UML - Muhammad Sahlan Novantoro; Sabilal Ilham; Shafa Maliha (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The rapid development of information technology has encouraged retail businesses to adopt web-based information systems to improve operational efficiency. This study aims to design a web-based purchasing information system for a watch retail store using the Unified Modeling Language (UML) approach. The research employs a Systematic Literature Review to identify best practices in purchasing system design and UML-based modeling. The system design process begins with an analysis of business processes and user requirements, followed by system modeling using use case, activity, sequence, and class diagrams. The results indicate that UML effectively represents system functionality, data structure, and user interaction in a clear and structured manner. The proposed system is designed to support purchasing transactions, supplier management, and automatic inventory updates in an integrated platform. Evaluation of the design shows that the system meets functional requirements and has the potential to reduce data errors, improve information accuracy, and support managerial decision-making. This study provides practical and theoretical contributions to the development of web-based purchasing information systems for retail businesses, particularly small and medium-sized enterprises.